Pertanggung Jawaban Pidana Korporasi atas Praktik Greenwashing dalam Kegiatan Usaha Berbasis Lingkungan - Rindang Gici Oktavianti; Syarifah Umami; Dini Riski Ramadhania (MLJ Merdeka Law Journal, 2026)
The development of the green economy has encouraged corporations to project environmentally friendly images in their business activities. However, this trend has also given rise to greenwashing, a practice of disseminating misleading information regarding the environmental sustainability of products or business operations. This study aims to analyze greenwashing from the perspective of corporate criminal liability and examine its legal regulation under Law Number 1 of 2023 on the Indonesian Criminal Code (KUHP), the Consumer Protection Law, and the Environmental Protection and Management Law. This research employs a normative juridical method with statutory and conceptual approaches, relying on the analysis of primary, secondary, and tertiary legal materials.